Addition of some non-indigenous elements to the flora of Marathwada regions, Maharashtra, India. - A, Kare M; Mule, D A; Paithane, V A; Bhuktar, A S (International Multidisciplinary Research Journal, 2013)
During our field survey, many taxa were collected from the Marathwada region. Specimens were brought to laboratory and processed for herbarium specimens with standard procedures. Majority of the specimens satisfactory identified by using pertinent literature. After critical investigations, authors found that six taxa are not earlier reported from the region. So present paper deals new records of six species with its correct and updated citation, short description and note on its phenology is depicted for each taxon followed by a note on ecology and images of all for easy identification.